Choice, price and service characteristics in the Irish broadband market - Seán Lyons; Michael Savage (The Economic and Social Research Institute (ESRI), 2012)
Abstract: Using detailed plan-level data, this paper examines the choice, price and quality of broadband services available to consumers in Ireland over time. We find modest geographical (county level) variation in broadband services. Hedonic regression analysis is used to value various components of the broadband service. Download and upload speed attract positive valuations, whereas contention ratio is valued negatively as expected. The results suggest that the marginal valuation of download speed decreases as the speed level increases, with little value currently placed upon speeds above about 60 Mb/s.
Keywords: 330; broadband services; market analysis; Ireland